The Application of Jigsaw type of Cooperative Learning Model to Improve Geography Learning Outcomes in SMA 3 Pinggir - Sri Marlina; Nofrion Nofrion; Iswandi Iswandi (Postgraduate School, Universitas Negeri Padang, 2020)
The problem in this research are; low student motivation, the learning ability of students in the lower, the ability of students to solve the problem of low, communication skills among students is less, the ability of students to understand the teaching materials is low. Classroom Action Research (CAR) aims to improve the learning outcomes of Geography through the application of the jigsaw type cooperative learning model. Based on the discussion, this classroom action research can be concluded that the application of a jigsaw cooperative learning model can improve Geography learning outcomes. This is proven by data analysis. Mastery learning students before improvement only amounts to 9 (30%) only. However, after improving the first cycle of student learning completeness can be increased to 24 (80%). Furthermore, improvement in the second cycle of student learning completeness can be increased again to 30 (100%). However, after an improvement in the first cycle, students' absorption capacity can be increased (87%). Furthermore, after making improvements in the second cycle, students' absorption capacity can be increased to (96%).